Archival sources of the old Vilnius University - Petrauskienė, Irena (Knygotyra, 1980)
Profound and manysided research of the past is possible studying primary sources only. Manuscript material saved in the Soviet Union as well as in other various countries presents such sources of Vilnius University history. The purpose of the article is to group this material in subjects, to characterize it, keeping to the principles of chronology and to point its location. The author touchs on subjects of the reclamation of these sources, surveys catalogues and reviews publications. In conclusion the author characterizes the most important research works refering to archival material about Vilnius University.